Emotional Experiences of Preschool Teachers During Learning Evaluation: A Phenomenological Study - Nuroniah, Pepi; Alfarisa , Fitri; Anesty Mashudi, Esya; Fatihaturosyidah, Fatihaturosyidah; Piyakun, Araya (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This study explores the emotional experiences of preschool teachers during the implementation of learning evaluations. Utilizing a qualitative phenomenological approach, the research captures the lived experiences of 18 preschool teachers in Banten, Indonesia. Data were collected through in-depth interviews and observations from April to December 2023, employing snowball sampling to ensure relevant expertise. Thematic analysis revealed that teachers predominantly experienced positive emotions, such as pride, joy, and gratitude, during the planning and preparation of evaluation instruments. However, negative emotions, including anxiety and discomfort, emerged during the implementation and follow-up stages. These negative emotions were often linked to concerns about meeting educational targets and managing classroom dynamics effectively. The study identifies that positive emotions were associated with the perceived importance of evaluation planning and successful execution, while negative emotions were connected to fears of underperformance and external pressures. These findings highlight preschool teachers' complex emotional landscape, emphasizing the need for professional development programs focusing on emotional regulation and stress management. The study's implications suggest that fostering a supportive school environment can enhance teachers' well-being and effectiveness, ultimately benefiting student outcomes. Limitations include the small, geographically limited sample and reliance on self-reported data, which may introduce bias. Future research should expand the sample size, incorporate diverse geographical locations, and utilize mixed-methods approaches to comprehensively understand teachers' emotional experiences. Such research would enable the development of more effective support strategies for educators, contributing to improved educational practices and teacher satisfaction.